PENINGKATAN PENGETAHUAN KESEHATAN REPRODUKSI REMAJA MELALUI PENYULUHAN KESEHATAN PADA SISWA SANGGAR BIMBINGAN (SB) AT TANZIL SERDANG, MALAYSIA - Dian Ayuningrum, Lia; Kholis Frendika; Hasna Widya Nastiti; Fatimatasari (Jurnal Berdaya Mandiri, 2024)
During adolescence, having knowledge about reproductive health is a very important aspect for the formation of healthy attitudes and behavior in adolescents. Lack of knowledge about reproductive health can have an impact on risky behavior, especially in adolescents who have limited access to information and health services. This activity aims to increase reproductive health knowledge among teenagers at the At-Tanzil Serdang Guidance Studio (SB), Malaysia, most of whom come from Indonesian Migrant Worker (PMI) families. This activity uses an interactive lecture method supported by media in the form of PowerPoint and educational videos. The ultrasound method ((Urgency, Seriousness, Growth) is applied to determine problem priorities, while the fishbone diagram is used to identify the root causes of low understanding of reproductive health in adolescents. Evaluation of counseling activities is carried out through pretest and posttest. The results show a significant increase in adolescents' understanding of reproductive health after counseling, the statistical test results showed a significant difference (p < 0.05). This activity is expected to have a long-term impact in helping teenagers maintain their reproductive health during puberty. Keywords: Reproductive health, adolescents, counseling, Guidance Studio